PEDAGOGICAL CONDITIONS OF BUILDING THE CULTURE OF ACADEMIC HO (EDUCATION IN THE 21ST CENTURY, 2023)
The article deals with the problem of the formation of academic honesty in the framework of continuing education. Violations of the rules of academic honesty are considered at the technical and technological levels. When highlighting the factors of theformation of academic honesty, it is emphasized the importance not only of the macro-, micro-, but also meso- and mega environment.Academic honesty is viewed not only in the context of education, but in the socialization of the individual. It is necessary to organize such a process of forming the competence of academic writing, which begins at school and continues at the university aftergraduation. Actual researches on this issue shows that within the framework of pedagogy and psychology, clear strategies and technologies for the formation of a culture of academic honesty have been developed. In modern research on the formation of a culture of academic honesty (Bogolepova 2016, Valeeva, Sirazeeva 2015, Demidova 2014, Korotkina 2015, Walmsley and Birkbeck 2006), great importance is attached to the formation of the pedagogical system of developing academic and reflective competences of students in the framework of continuing education.The purpose of this study is to present the pedagogical system of the formation of academic honesty in the RA.Novelty. The pedagogical problems of forming academic honesty in terms of developing effective strategies and technologies of training and education are highlighted, it is proposed to highlight political, psychological and pedagogical approaches to providingthe conditions for forming the culture of academic honesty at a higher reflex level.
Keywords: academic honesty; pedagogical conditions; culture; written word; quotation; reference; plagiarism; strategy; reflexive competence; critical analysis